Mycorrhizae set the stage for plants to produce a higher production of biomolecules and stress-related metabolites: a sustainable alternative of agrochemicals to enhance the quality and yield of beetroot (Beta vulgaris L.) - Yadav, Vinod Kumar; Kumar, Deepesh; Jha, Radha Krishna; Bairwa, Rakesh Kumar; Singh, Rajan; Mishra, Gaurav; Singh, Jyoti Prakash; Kumar, Adarsh; Vinesh, Banoth; Jayaswall, Kuldip; Rai, Abhishek Kumar; Singh, Arvind Nath; et al. (Frontiers in Microbiology, 2023)
Population explosions, environmental deprivation, and industrial expansion led to an imbalanced agricultural system. Non-judicial uses of agrochemicals have decreased agrodiversity, degraded agroecosystems, and increased the cost of farming. In this scenario, a sustainable agriculture system could play a crucial role; however, it needs rigorous study to understand the biological interfaces within agroecosystems. Among the various biological components with respect to agriculture, mycorrhizae could be a potential candidate. Most agricultural crops are symbiotic with arbuscular mycorrhizal fungi (AMF). In this study, beetroot has been chose to study the effect of different AMFs on various parameters such as morphological traits, biochemical attributes, and gene expression analysis (ALDH7B4 and ALDH3I1). The AMF Gm-Funneliformis mosseae (Glomus mosseae), Acaulospora laevis, and GG-Gigaspora gigantean were taken as treatments to study the effect on the above-mentioned parameters in beetroot. We observed that among all the possible combinations of mycorrhizae, Gm+Al+GG performed best, and the Al-alone treatment was found to be a poor performer with respect to all the studied parameters. This study concluded that the more the combinations of mycorrhizae, the better the results will be. However, the phenomenon depends on the receptivity, infectivity, and past nutrient profile of the soil.